Construction of ferrocene modified and indocyanine green loaded multifunctional mesoporous silica nanoparticle for simultaneous chemodynamic/photothermal/photodynamic therapy. (March 2021) - Han, Renlu; Wu, Sheng; Yan, Yuyan; Chen, Wei; Tang, Keqi
Abstract: Near-infrared (NIR) light responsive multifunctional nanoparticles were constructed by ferrocene modified, indocyanine green (ICG) loaded and β-cyclodextrin (β-CD) capped mesoporous silica (MSN) for collaborative chemodynamic/ photothermal/photodynamic (CDT/PTT/PDT) therapy in vitro. In the multifunctional nanoparticles, the covalently conjugated ferrocene was acted as a catalyst for converting the high level of intracellular hydrogen peroxide (H2 O2 ) into high-toxic hydroxyl radical ( OH), the encapsulated ICG was served as both photothermal agent and photosensitizer to generate hyperpyrexia and singlet oxygen ( 1 O2 ) respectively by absorbing NIR light, and the outmost β-CD was worked as a shielding layer to prevent ICG from leakage and improve the dispersity of as-prepared nanoparticles. After the nanoparticles were endocytosed by cancer cells, the hyperpyrexia generated by ICG upon NIR light irradiation not only is able to directly kill cancer cells for photothermal therapy (PTT), but also enables to dissociate the capped β-CD and thus expose the inner ferrocene. On this basis, the exposed ferrocene could convert the intracellular H2 O2 into toxic OH via ferrocene-mediated Fenton reaction for efficiently killing cancer cells (chemodynamic therapy, CDT). Moreover, the generated 1 O2 by ICG could further kill the cancer cells for photodynamic therapy (PDT) in a collaborative way. The results of in vitro experiments suggest that the collaborative CDT/PTT/PDT shows significantly amplified inhibition rate of HeLa cells compared to single CDT or dual PTT/PDT, endowing the multifunctional nanoparticles with great potential in cancer synergistic treatments.